Pemenuhan Aksesibilitas Hak Politik Bagi Difabel Dalam Pemilukada 2015 (Studi tentang Aksesibilitas Difabel dalam pelaksanaan Pemilukada di Kabupaten Sragen) - YUHANDA, Ferry, Iswanto, SH, M.H, Jaka Susila, SH, M.Si, M.H (2017)
This research was conducted with the aim to determine the legal basis of legal protection for the disabled in the fulfillment of their political rights to the accessibility of the election in the area simultaneously in Sragen 2015. And to know the extent of ensuring that compliance with the accessibility of political rights for the disabled in the field as it has been mandated by regulations legislation in force. This study uses a descriptive, because it intends to describe clearly on various matters related to the object under investigation, which is about how the Act protects the fulfillment of accessibility rights to politics for the disabled in the election and how the implementation of compliance with the accessibility of the right to political for the disabled in Election activities of regional heads simultaneously in Sragen year 2015. writing this essay basing on legal research conducted by non-doctrinal approach is qualitative. Necessary data in this study, will be collected in two ways: through the study of literature and interviews directly to the speakers and the parties related to the issues discussed and the study of literature. Ensuring that compliance with the accessibility of political rights for Disability in the election of Regional Head General Simultaneously in Sragen has terinventarisasi in a variety of legislation ranging from the Constitution of the Republic of Indonesia Year 1945 to the Regional Regulation Sragen No. 14 of 2014 on the implementation of the protection of persons with disabilities, however for some parties considered not evenly distributed and fully implemented appropriately.